The Role of Ambiguity Tolerance and Enthusiasm on Chinese University Teachers’ Burnout - Yang, Yan; Xie, Juan (Frontiers in Psychology, 2022)
Educators face numerous vague conditions in their daily practice and they must manage students with diverse characters that lead to burnout. In addition, tolerance of ambiguity is a term used by educators as the capability to control new, complicated or insoluble situations. Moreover, educator enthusiasm and its effect on instruction was neglected. And due to the essential function that teachers’ burnout plays in the efficiency of their achievement in the scholastic cycle, the present study inspected whether the above-mentioned constructs such as teachers’ ambiguity tolerance and enthusiasm can influence their burnout on one hand and on the other hand if these constructs can predict the teachers’ burnout or not. For the objective of the study, a group of 495 female and male Chinese university teachers in 18 provinces of China were asked to fill out the three scales, namely, teacher enthusiasm, ambiguity tolerance, and burnout. The primary results of the research, achieved through running Spearman Rho, specify that there are constructive relationships between ambiguity tolerance, enthusiasm and by employing multiple regression analysis; it is revealed that both variables, namely ambiguity tolerance, enthusiasm were the predictors of teachers’ burnout, while ambiguity tolerance was a better predictor. Accordingly, based on these findings, it can be concluded that both of these factors affect teachers’ burnout in the teaching process. In addition, this study can provide additional implications for academic scholars and experts in academic settings.